English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

w^2-w = w( )

2006-11-30 04:01:54 · 4 answers · asked by kris10 1 in Science & Mathematics Mathematics

4 answers

w(w-1)

2006-11-30 04:03:15 · answer #1 · answered by jennytkd13 3 · 1 0

w^2-w = w( )

w^2-w = w(w-1)
(and the expression in the parenthesis is w-1)

Work:
note that w^2 = w*w, so the w^2 - w
can be expressed also as w*w - w!
Now, on the left, extract the common multiplier from both w^2 and w:
w(w-1)

you get:
w(w-1) = w()

since w = w,
(w-1) = ()
the expression in parenthesis is w-1, and the solution is:
w^2-w = w(w-1)

2006-11-30 14:52:07 · answer #2 · answered by Mirta G 2 · 0 0

w^2-w = w( )

We're looking for the Greatest Common Factor, GCF.
In this case, w^2-w has a GCF=w.

w[(w^2)/w - w/w]

Simplify & Reduce:

w(w-1)

ANSWER:
w^2-w = w(w-1)

2006-11-30 12:26:53 · answer #3 · answered by LovesMath 3 · 0 0

(w-1)

2006-11-30 12:06:05 · answer #4 · answered by ? 3 · 0 0

fedest.com, questions and answers